(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis analyzes scientifically grounded mechanisms for improving the quality of social services in Uzbekistan through the development of a competitive environment in the social services market. The aim of the study is to develop a step-by-step framework for transitioning from the existing state-centered model to a consumer-oriented, transparent, and results-based competitive system. Using a systematic approach, statistical analysis, correlation analysis, and expert evaluation methods, the study proposes an integrated mechanism that includes simplifying market entry, ensuring consumer choice through electronic vouchers and open rating systems, linking state procurement to performance indicators, and introducing independent accreditation monitoring.